The Sponges of the Carmel Pinnacles Marine Protected Area - Turner, Thomas L.; Lonhart, Steve I. (Zootaxa, 2023)
California’s network of marine protected areas was created to protect the diversity and abundance of native marine life, but the status of some taxa is very poorly known. Here we describe the sponges (phylum Porifera) from the Carmel Pinnacles State Marine Reserve, as assessed by a SCUBA-based survey in shallow waters. Of the 29 sponge species documented, 12 (41%) of them were previously unknown. Using a combination of underwater photography, DNA sequencing, and morphological taxonomy, we greatly improve our understanding of the status and distribution of previously described species and formally describe the new species as Hymedesmia promina sp. nov., Phorbas nebulosus sp. nov., Clathria unoriginalis sp. nov., Clathria rumsena sp. nov., Megaciella sanctuarium sp. nov., Mycale lobos sp. nov., Xestospongia ursa sp. nov., Haliclona melissae sp. nov., Halichondria loma sp. nov., Hymeniacidon fusiformis sp. nov., Scopalina carmela sp. nov., and Obruta collector gen. nov., sp. nov. An additional species, Lissodendoryx topsenti (de Laubenfels 1930), is moved to Hemimycale, and H. polyboletus comb. nov., nom. nov. is created due to preoccupation by H. topsenti (Burton, 1929). Several of the new species appear to be rare and/or have very restricted distributions, as they were not found at comparative survey sites outside of Carmel Bay. These results illustrate the potential of qualitative presence/absence systematic surveys of understudied taxa to discover and document substantial novel diversity.